2020
DOI: 10.3390/ani10112150
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Selected Phytobiotics with Halquinol and Tetracycline on Gut Morphology, Ileal Digestibility, Cecal Microbiota Composition and Growth Performance in Broiler Chickens

Abstract: The current experiment was designed to estimate the comparative efficacy of selected phytobiotics Persicaria odorata leaf meal (POLM) and Piper betle leaf meal (PBLM) with halquinol, and tetracycline in broiler chickens. The 150-day-old broiler chickens were randomly assigned to five dietary groups. The dietary supplementation groups were the basal diet (BD), which served as the negative control (NC), and BD + 0.2 g/kg tetracycline, which served as the positive control (PC); BD + 0.03 g/kg halquinol (HAL), BD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 101 publications
1
15
1
1
Order By: Relevance
“…Particularly, unlike for C. frutescens as observed in this study, no effects on proventriculus weights have been reported in the case of C. annuum, (Islam et al, 2018). Besides Capsicums, other phytogenics whose effects on internal organs of chicken have been investigated include Myristica fragrans (Adu et al, 2020), Persicaria odorata (Basit et al, 2020), fenugreek seeds (Hashim et al, 2019), paw paw latex (Haruna and Odunsi, 2018), ginger (Qorbanpour et al, 2018) and garlic (Islam et al, 2018). Positive effects on proventriculus have been reported for garlic when used at 0.75% whereas no influence on weights of internal organs has been observed for Myrisitca fragrans and Persicraia odorata (Islam et al, 2018;Adu et al, 2020;Basit et al, 2020).…”
Section: Carcass Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, unlike for C. frutescens as observed in this study, no effects on proventriculus weights have been reported in the case of C. annuum, (Islam et al, 2018). Besides Capsicums, other phytogenics whose effects on internal organs of chicken have been investigated include Myristica fragrans (Adu et al, 2020), Persicaria odorata (Basit et al, 2020), fenugreek seeds (Hashim et al, 2019), paw paw latex (Haruna and Odunsi, 2018), ginger (Qorbanpour et al, 2018) and garlic (Islam et al, 2018). Positive effects on proventriculus have been reported for garlic when used at 0.75% whereas no influence on weights of internal organs has been observed for Myrisitca fragrans and Persicraia odorata (Islam et al, 2018;Adu et al, 2020;Basit et al, 2020).…”
Section: Carcass Yieldmentioning
confidence: 99%
“…Besides Capsicums, other phytogenics whose effects on internal organs of chicken have been investigated include Myristica fragrans (Adu et al, 2020), Persicaria odorata (Basit et al, 2020), fenugreek seeds (Hashim et al, 2019), paw paw latex (Haruna and Odunsi, 2018), ginger (Qorbanpour et al, 2018) and garlic (Islam et al, 2018). Positive effects on proventriculus have been reported for garlic when used at 0.75% whereas no influence on weights of internal organs has been observed for Myrisitca fragrans and Persicraia odorata (Islam et al, 2018;Adu et al, 2020;Basit et al, 2020). In contrast, negative effects have been noted with respect to lowering giblets percentage in the case of fenugreek seeds (Hashim et al, 2019) and hypertrophy of gizzard, liver and intestines associated with paw paw latex (Haruna and Odunsi, 2018).…”
Section: Carcass Yieldmentioning
confidence: 99%
“…Phytogenics contain active ingredients with interesting functional properties such as antimicrobial activity, avoiding the adhesion of pathogens to intestinal mucosa and modulating gut microbiota [ 11 , 12 ]. Therefore, phytogenics can minimize the risk of development of pathogens [ 12 ], and the changes in digestive function induce the growth of beneficial bacteria such as Lactobacillus or bifidobacteria [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, 30 mL of preculture was prepared by picking a single colony into sterile pre-warmed tryptone soy broth and incubating the mixture at 37 °C with orbital shaking for 24 h. Subsequently, 10 mL of Salmonella enteritidis preculture was transferred into 300 mL of sterile tryptone soy broth, and the mixture was incubated in an orbital shaker at 37 °C for 16 h. The number of colony-forming units (CFU) was determined with a tenfold dilution series in sterile buffered 0.9% peptone water with a pH of 7.2. The stock culture was adjusted to 1 × 10 7 CFU by centrifuging at 3,000 rpm and 4 °C for 10 min40 . The Salmonella solution was freshly prepared before oral gavage.…”
mentioning
confidence: 99%
“…The Salmonella solution was freshly prepared before oral gavage. A pilot trial was conducted to ascertain the appropriate dose administrated to broilers40 (Supplement 1. pilot trial).…”
mentioning
confidence: 99%